2008
DOI: 10.1158/1078-0432.ccr-08-0403
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Cancer Other Than Melanoma in CDKN2A Founder Mutation (p16-Leiden)-Positive Melanoma Families

Abstract: Purpose: We report the largest study to date analyzing the risk of cancers other than melanoma in melanoma families positive for the same CDKN2A mutation. Experimental Design: We studied family members of 22 families positive for the p16-Leiden founder mutation who had attended a surveillance clinic or were their close relatives. Within this cohort, observed and expected rates of cancer were computed by mutation status consisting of 221 (proven plus obligate) carriers, 639 (proven plus obligate) noncarriers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 25 publications
2
109
4
4
Order By: Relevance
“…8,14 There are several potential explanations for this difference. A reporting bias could exist (over reporting in pancreatic kindreds or underreporting in melanoma kindreds), and our study is limited by relying on proband report of cancer among relatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,14 There are several potential explanations for this difference. A reporting bias could exist (over reporting in pancreatic kindreds or underreporting in melanoma kindreds), and our study is limited by relying on proband report of cancer among relatives.…”
Section: Discussionmentioning
confidence: 99%
“…7 Brain, head/neck and nonmelanoma skin cancer have also been reported to be more common among mutation carriers. [8][9][10] The CDKN2A gene encodes two different proteins, read from alternate reading frames of a common second exon. The portion of the gene that encodes p16 is composed of three exons, and p16 is a recognized tumor suppressor because of its role in preventing progression through the G1 cell cycle checkpoint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous retrospective study by de Snoo et al 6 also found significantly increased risks for these tumours in a cohort of p16-Leiden variant carriers. Oldenburg et al 15 described a p16-Leiden variant-positive family in which many relatives had developed lung cancer and head and neck tumours.…”
Section: Discussionmentioning
confidence: 71%
“…5 Several studies reported an increased risk of tumours other than melanoma and pancreatic cancers for various CDKN2A germline variants. [6][7][8][9][10] However, these studies have used a variety of methodological approaches and some have been limited by inclusion of heterogeneous groups or by failure to determine individual mutation status. In addition, the influence of environmental factors (for example, smoking) on the phenotypic variability in FAMMM syndrome is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%